National imaginaries on the Peruvian Indian: José Uriel García within intellectual networks during the first decades of the 20th century - Villanueva Ccahuana, Philarine Stefany (2021)
This paper aims to demonstrate the positioning and legitimation of the aesthetic-ideological project of the “new Indian”, theorized by the Cusco’s essayist José Uriel García, based on the intellectual networks that were being configured in the first decades of the 20th century. Our critical historical methodology is based on the analysis of texts whose meanings are in dialogue with the historical moment of their production and with the intellectual field of the period. Our main object of study is the essay The New Indian (1930), by the Cusco’s ideologue. It was found that, as opposed to the more purist national imaginary of the indigenous, based on past evocations (especially Inca times) of hegemonic indigenism, Uriel García’s approach emerged as a project of rupture from his contemporary vision of the Indian. We consider this did not imply lack of interest in the Indian of the past, but rather a more complex aesthetic-ideological position in which critical categories with semantic density such as “mestizaje espiritual” or “indianidad” come into play.